Effects of recombinant human brain natriuretic peptide in patients with acute myocardial infarction undergoing percutaneous coronary intervention: A systematic review and meta-analysis. Issue 11 (March 2020) - Ning, Cheng; Zheng, Yawei; Li, Jie; Liu, Ming; Fang, Zhuyuan
Abstract: Objective: To systematically review the effect of recombinant human brain natriuretic peptide (rhBNP) on the cardiac function in patients with acute myocardial infarction (AMI) undergoing percutaneous coronary intervention (PCI). Methods: PubMed, Web of Science, the Cochrane Library, Chinese Biomedical Database (CBD), and China National Knowledge Infrastructure (CNKI) were electronically searched to collect randomized controlled trials (RCTs) of traditional exercise for patients with AMI undergoing PCI from the beginning of the database inception to January 2019. Two reviewers independently screened the literature, extracted data, and evaluated the quality of included studies. Then, meta-analysis was performed using the RevMan 5.3 software. Results: A total of 16 RCTs and 1551 patients were included. The results of the meta-analysis showed that, compared with the control-treated patients, rhBNP-treated patients with AMI had an increased left ventricular ejection fraction (LVEF) of 3.34% ([MD = 3.34, 95% CI (0.39, 6.29), P  = .03]) 1 week postoperatively, 6.22% ([MD = 6.22, 95% CI (4.15, 8.28), P < .00001]) 4 weeks postoperatively, 7.34% ([mean difference (MD) = 7.34, 95% CI (4.52, 10.16), P < .00001]) 12 weeks postoperatively, and 5.32% ([MD = 5.32, 95% CI (3.05, 7.59), P < .00001]) 24 weeks postoperatively. Moreover, the heart failure (HF) recurrence of rhBNP-treated patients with AMI 12 weeks postoperatively was 0.24 times that of the control-treated patients ([risk ratio (RR) = 0.24, 95% CI (0.06, 0.92), P  = .04]), and the difference was statistically significant. At the same time, rhBNP-treated patients had decreased N-terminal pro-brain natriuretic peptide (NT-proBNP) (24 hours, 48 hours, 72 hours) and aldosterone (Ald) (24 hours, 72 hours, 168 hours) levels in comparison with the control-treated patients. Conclusion: Current evidence shows that the application of rhBNP presents a greater clinical benefit to patients with AMI undergoing PCI. Due to the methodological bias in the included studies and small sample size, more high-quality studies are required to verify the study findings. Systematic Review Registration Number: PROSPERO (CRD42019126727)